The Effect of Students' Responses to Instructional Videos is Associated with Motivation and Responsibility - Nugraha, Ugi; Ilham; Harjono, Hary Soedarto; Setiawan, Aji (Journal of Education Technology, 2022)
Currently students really need a learning media that facilitates the learning process, one of the effective learning media used by students is video learning to increase student motivation and responsibility. This study aims to find out how the statistical results and differences as well the influence of students on student response variables, motivation, and responsibility in PJOK subjects in high school will be useful as a benchmark in improving student responses, motivation and student responsibility through learning videos and can be used as a reference in further research. The number of respondents as a sample is 140 students. this research method is a research and development model of R&D (Research and Development). The data collection technique used random sampling. The results of the study using a regression test that there is an influence between learning videos on student responses to student motivation and responsibility. so it can be said that the learning video is very influential on student responses to motivation and student answers on PJOK subjects at the secondary school level. The implication of this research is that student response is very important for motivation and responsibility so that it can be implemented in student learning outcomes. Thus, a good student response to student motivation and responsibility will improve student learning outcomes in high school.